2018
DOI: 10.1021/acs.jpclett.8b01897
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Conversion of Nitrogen Trifluoride as a Gas-to-Solid Cathode in Li Batteries

Abstract: Nonaqueous metal-gas batteries have emerged as a growing family of primary and rechargeable batteries with high capacities and energy densities. We herein report a high-capacity primary Li-gas battery that uses a perfluorinated gas, nitrogen trifluoride (NF), as the cathode reactant. Gravimetric capacities of ∼1100 and 4000 mAh/g are achieved at 25 and 55 °C, respectively (at 20 mA/g), with discharge voltages up to 2.6 V vs Li/Li. NF reduction occurs by a 3e/NF process, yielding polycrystalline lithium fluorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 37 publications
(64 reference statements)
2
13
0
2
Order By: Relevance
“…Among various solid cathode materials, fluorinated carbon (CF x ) has attracted unprecedent attention due to their high theoretical energy density, which is much higher than that of lithium ion batteries (~500 W h kg −1 ) [3]. To fill this short-term technology gap for producing batteries with higher energy densities, several types of nonaqueous metal-gas batteries have been explored to meet growing demands, such as Li-O 2 [4], Na-O 2 [5], K-O 2 [6], Li-CO 2 [7,8], Li-NF 3 [9], and Li-SF 6 [10][11][12]. However, the gas-to-solid conversion reaction involves a solution-mediated electrochemical process that induces complex thermodynamics, kinetics, and transport considerations, and it remains a challenge to achieve the potential energy densities and realize practical applications for these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Among various solid cathode materials, fluorinated carbon (CF x ) has attracted unprecedent attention due to their high theoretical energy density, which is much higher than that of lithium ion batteries (~500 W h kg −1 ) [3]. To fill this short-term technology gap for producing batteries with higher energy densities, several types of nonaqueous metal-gas batteries have been explored to meet growing demands, such as Li-O 2 [4], Na-O 2 [5], K-O 2 [6], Li-CO 2 [7,8], Li-NF 3 [9], and Li-SF 6 [10][11][12]. However, the gas-to-solid conversion reaction involves a solution-mediated electrochemical process that induces complex thermodynamics, kinetics, and transport considerations, and it remains a challenge to achieve the potential energy densities and realize practical applications for these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen trifluorida (5)(6)(7)(8)(9) adalah suatu senyawa anorganik dengan rumus NF 3 . Senyawa nitrogen (13)(14)(15) fluor (16)(17)(18) ini adalah gas tak berwarna, tak berbau dan tidak mudah terbakar.…”
Section: Kesimpulanunclassified
“…Nitrogen trifluorida (5)(6)(7)(8)(9) adalah senyawa anorganik (11; 12) dengan rumus molekul NF 3 . NF 3 merupakan senyawa yang tidak berwarna, tidak berbau, gas mudah terbakar.…”
Section: Introductionunclassified
“…To test this hypothesis, and to examine another possible fluoridation methodology with potential to help elucidate the limitations of those used so far, this study investigated whether higher degrees of fluoridation, as evidenced by higher discharge capacities, are achievable using an electrochemically sourced LiF formed by reduction of perfluorinated gases. Recently, we have found that the full reduction of SF 6 (SF 6 + 8e À + 8Li + !Li 2 S + 6LiF) [13] and NF 3 (NF 3 + 3e À + 3Li + !3LiF + 1 = 2 N 2 ) [14] occurs on carbon cathodes at potentials of 2-3 V vs. Li/Li + , thus the gases act as a highly-F-dense and electroactive molecular LiF source. Moreover, the morphology of the electrochemically formed LiF, which nucleates and grows as nanoscale particles (with diameters ranging from 20 nm to > 400 nm) on the cathode substrate, was found to be highly versatile and could be tailored by modulating conditions such as electrolyte, discharge rate, and capacity.…”
Section: Introductionmentioning
confidence: 99%